Analisis Faktor - Faktor Yang Mempengaruhi Produktivitas Tenaga Kerja di Indonesia - Mesi Mukhlisiana; Melti Roza Adry (Universitas Negeri Padang, 2021)
This study aims to determine the effect of wages, education and health on labor productivity in Indonesia. This study uses panel data on 34 provinces in Indonesia.The results of the data were obtained from the Central Statistics Agency. This research uses Panel Regression Analysis. The results of this study indicate that (1) Wages have a significant effect on the productivity of Indonesia workers, (2) Education has no significant effect on the productivity of Indonesia workers and (3) Healty has a significant effect on the productivity of Indonesia workers.